Adult Development and Aging - Diane E. Papalia, Harvey L. Sterns (Mc Graw Hill, 2007)
The third edition provides a positives perspective on adult development and aging, enhances by strong multicultural and diversity coverage. and also includes new content on younger and middle-aged adults, providing a better balance between adulthood and aging.